The fluidization of group C particles: the effect of binary mixture / Rosdan Ramli - Ramli, Rosdan (2002)
Experimental works to study the fluidization of group C particles in term of the effect of binary mixture were carried out. This binary mixtures which consist of fines group C glutinous flour and group B sand particles were fluidized in a fluidized bed with a diameter and height of 0.05m and 0.9m respectively. In this experiment, two methods of mixing were used. The first method was performed by mixing the flour with sand randomly and the second method was carried out by placing the sand as a separate layer at the bottom and the cohesive particles on top of the sand in the column. Three different percentages of a sand were used i.e. 10%w/w, 20%w/w and 30%w/w and preliminary experiments where the properties of base element such as bulk density, tapped density, aerated density as well as sieve analysis of the sand and glutinous flour used were also obtained. The experiment indicated that application of different mixing method could lead to different behaviour of fluidization.